The Pyruvate-Phosphate Dikinase (C4-SmPPDK) Gene From Suaeda monoica Enhances Photosynthesis, Carbon Assimilation, and Abiotic Stress Tolerance in a C3 Plant Under Elevated CO2 Conditions - Yadav, Sonam; Rathore, Mangal Singh; Mishra, Avinash (Frontiers in Plant Science, 2020)
A pyruvate-phosphate dikinase (C4-PPDK) gene was cloned from Suaeda monoica, which had a single-cell C4 photosynthesis pathway without Kranz anatomy and was functionally validated in a C3 model plant under different abiotic stress conditions in an ambient and elevated CO2 environment. Overexpression of SmPPDK promoted growth of C3 transgenic plants, enhancing their photosynthesis (CO2 assimilation) by lowering photorespiration under stress conditions. Transgenic plants also showed an improved physiological status, with higher relative water content (RWC), membrane integrity, concentration of glycine betaine, total soluble sugars, free amino acids, polyphenols and antioxidant activity, and lower electrolyte leakage, lipid peroxidation, free radical accumulation, and generation of reactive oxygen species (ROS), compared to control plants. Moreover, SmPPDK transgenic plants exhibited earlier flowering and higher dry biomass compared to controls. These results suggested that the C4-PPDK gene was appropriate for improvement of carbon assimilation, and it also played an important role in adaption to salinity and severe drought-induced stress. More intriguingly, an elevated CO2 environment alleviated the adverse effects of abiotic stress, particularly caused by drought through coordination of osmoprotectants and antioxidant defense systems. The molecular, physiological, metabolic, and biochemical indicators ameliorated the overall performance of model C3 plants overexpressing the C4-PPDK gene in an elevated CO2 environment, by lowering photorespiration metabolic processes, however, further studies are needed to confirm its precise role in C3 plants as protection against future climate change.